ICT and the ubiguitous church missions: the emerging religious space on social media (2022)
Religion and Science have played important roles in human history, and have also shared a unique history because of the peculiarity and importance of the two fields and their exceptional relationship. Information and Communications Technology (ICT) is a product of Science and it has proved to be a sine qua non in all areas of existence. As Science, is progressing through ICT, the recognition, as well as the usage of social media is enormous in the 21st Century. The Nigerian society, both in public spaces and private spaces, is not left out of the massive use of social media such as Twitter, Facebook, WhatsApp, Linkedln, Instagram, Snapchat, Telegram, Perescope, 2go and the likes. Thus, social media wield a lot of influence in the society today, and like other aspects of living, it is being used in the propagation of religion by removing constraints of space and time, making both the message and messenger of religion highly ubiquitous. However, there is scant attention on the examination of the religious space within social media, especially in the Nigerian experience, thereby creating a lacuna this research intends to fill. This study seeks to examine the subject of "religious space" in social media and its emergence over time in this ICT-driven age, with the view to discussing its roles in church missions, the challenges associated with it, and the implications for church missions' policies.